Understanding Chinese families a comparative study of Taiwan and Southeast China - Chu, C. Y. Cyrus; Yu, Ruoh-Rong. (Oxford : Oxford University Press, 2010)
This text provides the reader with a comprehensive introduction to the distinguishing features of Chinese families.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Families -- China, Southeast; Families -- Taiwan; Family demography -- China, Southeast; Family demography -- Taiwan; China, Southeast -- Social policy; Taiwan -- Social policy; China, Southeast -- Economic conditions; Taiwan -- Economic conditions